“Living nature must be to the fore”. A study of the Dictionary of Pedagogy (1936) by the publisher Editorial Labor and the teaching of physics, chemistry and natural sciences - Corell Domenech, Mavi (Historia y Memoria de la Educación, 2021)
We present the study of one of the great projects of the Barcelona publisher Editorial Labor, namely the Diccionario de Pedagogía (1936), from a new perspective: the analysis of entries on the teaching of scientific subjects. The axis of the methodologies proposed by the work is the study of living things in their natural environment from an ecological perspective, both outside the classroom via excursions and inside through aquaria, terraria, herbaria and school kitchen gardens. These methodologies can be seen to have been be influenced by New Education principles, the English Nature Study movement and the Spanish Institución Libre de Enseñanza. Coordinated by Luis Sánchez Sarto, the Diccionario de Pedagogía recorded the state of pedagogy and education worldwide, counting on a hundred or so anonymous authors most of whom were German, Austrian, American or Spanish. John Dewey, Vilhelm Rasmussen and Georg Kerschensteiner are the dictionary’s pedagogical references in science teaching. In our article, we present arguments suggesting that Margarita Comas Camps and Rafael Candel Vila were the authors of the dictionary’s two entries on teaching methodology.